A novel method for in situ growing Ge-rich polycrystalline SiGe thin films on glass at low temperature. (October 2015) - Tao, Ke; Wang, Jin; Jia, Rui; Sun, Yun; Jin, Zhi; Lin, Xinyu
Graphical abstract: Abstract : In this paper, a novel method has been presented to fabricate Ge-rich poly-SiGe thin films on glass by chemical vapor deposition at temperatures as low as 300 °C. The nucleation mechanism of Ge on insulator has been investigated and the crystal quality of poly-SiGe has been confirmed by Raman spectra, XRD and TEM analyses. The results indicate that the poly-SiGe thin films fabricated by this method are applicable for SiGe-based electronic and optical devices on inexpensive substrates. Moreover, fabrication of high quality poly-SiGe thin films on a-Si thin film enables the application in multi-junction solar cell as the bottom cell.